Interactive effects of NPK fertilizer and paclobutrazol concentration on growth and yield of hanjeli (Coix lacryma-jobi L.) - Bafiqi, Medita Johana Pakula; Nurmala, Tati; Kadapi, Muhamad (Universitas Padjadjaran, 2023)
The balance between growth and crop yield can be manipulated by exploiting nutrient and retardant interactions. This study is aiming to assess the effects of various combinations of NPK 16-16-16 fertilizer in different doses, along with the application of multiple concentrations of paclobutrazol on the growth and yield of hanjeli. This experiment was carried out in the experimental field of Ciparanje, Faculty of Agriculture Universitas Padjadjaran, Jatinangor, Sumedang from February 2021 to August 2021. This research was conducted in a split-plot design with three replications. The main plot consisted of 200 kg ha-1, 250 kg ha-1, and 300 kg ha-1. The subplot consisted of 2000 ppm, 3000 ppm, and 4000 ppm. The results show that there were interaction effects between different doses of NPK fertilizer and paclobutrazol concentrations on plant height and 100-grain weight. The best combination came from the application of 200 kg/ha NPK fertilizer with 3000 ppm of paclobutrazol, which gave higher results in plant height and 200 kg/ha NPK fertilizer with 2000 ppm of paclobutrazol on 100-grain weight.